Xenon arc photocoagulation for the treatment of diabetic maculopathy. Interim report of a multicentre controlled clinical study. Issue 6 (June 1980) - Townsend, C; Bailey, J; Kohner, E
Abstract : The results of a randomised controlled clinical study in the treatment of diabetic maculopathy are reported. Ninety-nine patients with two similarly affected eyes had one–chosen by random procedure–treated, while the other was left as an untreated control. Visual acuity was maintained in the treated eyes, while it deteriorated in the untreated eyes, reaching over 2 lines difference after 4 years. The difference in deterioration was significantly less in treated than in untreated eyes at each assessment. After 4 years the difference between the 2 eyes was greatest in those with initially good vision. There was no difference in visual acuity in patients whose initial vision was less than 6/36. Only 9 treated but 25 control eyes lost vision to blindness (P less than 0.001). It is concluded that maculopathy is a treatable form of diabetic retinopathy if treated before severe visual loss occurs.